Model Pendampingan Koperasi Dalam Upaya Akselerasi Pencapaian Koperasi Modern - Restiany, Devi; Irawan, Dandan; Supriyadi, Deddy; Riyadhi Prayanda, Ibnu (Coopetition : Jurnal Ilmiah Manajemen, 2025)
Intervention efforts in dealing with the problems of modern cooperatives focus on priority needs, and one method is through assistance programs.This research uses qualitative methods with data collection techniques in the form of interviews, document analysis, observation, and triangulation. The results show that the 2023 modern cooperative assistance program is "Problem-Based Assistance", activities are carried out through pre-assistance, assistance, and post-assistance stages. The advantage of this mentoring model is that it has an inclusive nature, that is, it opens up opportunities for every cooperative to join in the Modern Cooperative Assistance program. The assistance begins with "determining the needs of the cooperative", namely an initial analysis carried out by the PMO (Project Management Office) team, and the existence of an assessment working paper and final assessment as an assessment indicator and a guide for assistants and participants in modern cooperatives. Based on the research results, there is a Recommendation for a Modern Cooperative Assistance Program Model, with several additions compared to the initial model, namely increasing the intensity of involvement of the Local Cooperative Government in charge of Cooperatives in the area where the Cooperative is located, as well as adding Post-Assistance activities in the form of Monitoring and Follow-up Mentoring activities which can be carried out by the Ministry or Local Cooperative Government so that this assistance model can help accelerate the achievement of Modern Cooperatives.